Design of Controllers using Fast Output Sampling Feedback – FOS for 1 & 2-link FMs - Milind, Joshi Shubangi; G., Dr. Arunkumar; Manjunath, Dr. T.C. (International Journal of Advanced Science and Technology, 2019)
The highlight of this research article is the design & development of Controllers using FOS for 1 & 2-link FMs is being presented for the control of a 2-link flexible robotic manipulator in the 3 Dimensional Euclidean space along with the simulation results.  A 2-link FM with 2-DOF is being considered in this research article and the base motor is attached to the single flexible link & the other link being attached @ the far end of the 1st link to which the shoulder motor is connected and the entire set-up is a single structure one and 2 motors are being used for actuation purposes & is being controlled / regulated using the developed sliding mode controller, i.e., the dual links are revolving around the base, further the link-2 is rotating w.r.t. the shoulder axes & the joint axes of the two are parallel and perpendicular w.r.t. the robot work surface.  Hence, the entire system can be called as a planar mechanism, i.e., the 2 links are moving parallel to the plane of the work surface (x – y plane). There are 2 joints, viz., base joint & the shoulder joint along with the end-effector being the tip of the 2-link manipulator. The small errors that occurs in the control signal u is due to the changes during the set-point.  Simulink model is being developed in the Simulink-MATLAB environment & the results of the MATLAB simulation are observed after the model is being run, from the obtained results thus showing the efficacy of the methodology developed by us.